Work Engagement di Karyawan: Peran Resiliensi dan Burnout dalam Industri Furnace - Devi Maharani Dwi Arti; Yanto Prasetyo; Hikmah Husniyah Farhanindya (JIWA: Jurnal Psikologi Indonesia, 2026)
Work engagement may be defined as a positive mental state indicating complete involvement in one's professional activities. The objective of this study is to ascertain the relationship between resilience and burnout, on the one hand, and work engagement, on the other, among employees in the head office of a mining services company specialising in furnace, kiln, and demolition services. The present study employed a quantitative approach, utilising a correlational design. A total of 50 students participated in the study by means of a technique known as "sample saturation". The data were collected using three psychological measurement tools and subsequently analysed with multiple linear regression. The findings of the present study demonstrate a substantial and direct relationship between resiliensi and burnout, both of which are concepts that are concurrently associated with work engagement. The relationship between resilience and work engagement is positive, while the relationship between burnout and work engagement is negative. The present study hypothesises that levels of work engagement are elevated in instances of resiliensi and diminished in instances of burnout.Keywords: Burnout; Employee; Resilience; Work Engagement.Work engagement adalah kondisi mental positif yang menunjukkan keterlibatan karyawan secara penuh dalam pekerjaan. Penelitian ini bertujuan untuk mengetahui hubungan antara resiliensi dan burnout dengan work engagement pada karyawan head office di perusahaan jasa pertambangan yang bergerak di bidang furnace, kiln, dan demolition. Penelitian menggunakan pendekatan kuantitatif dengan desain korelasional. Sebanyak 50 karyawan menjadi partisipan melalui teknik sampel jenuh. Data dikumpulkan menggunakan tiga alat ukur psikologis dan dianalisis dengan regresi linear berganda. Hasil penelitian menunjukkan bahwa resiliensi dan burnout secara simultan berhubungan signifikan dengan work engagement. Resiliensi memiliki hubungan positif, sedangkan burnout memiliki hubungan negatif terhadap work engagement. Penelitian ini menyimpulkan bahwa work engagement karyawan cenderung lebih tinggi ketika resiliensi meningkat dan burnout menurun.Kata kunci: Burnout; Karyawan; Resilience; Work Engagement.